Heterogeneity in Price Rigidity: Evidence from a Case Study Using Micro-Level Data - Daniel Levy; Shantanu Dutta; Mark Bergen (Bar-Ilan University, Department of Economics, 2002)
We combine two data sets to study price rigidity. The first consists of weekly time series of retail, wholesale, and spot prices for twelve products. These time series contain two exogenous cost shocks. We find that prices exhibit more rigidity in response to the second shock than the first. The second data set consists of all publicly available information about the shocks. Content analysis of these information reveals that the first shock is larger and more persistent, and the market has more information on it than the second. We conclude, therefore, that prices are more flexible in response to cost shocks that are larger, that are more persistent, and on which market participants have more information.
Keywords: E12; E31; L16; 330; price rigidity; cost shock; shock persistence; market information